The Entrepreneurship, Socioeconomic Factors, and Motivation in Project-Based Learning Success: The Mediating Role of Self-Efficacy - Nainggolan, Romauli; Yuli Kartika Dewi (ILIN Institute Makassar, 2025)
Project-based learning has become one of the most favored learning methods in schools and universities. Therefore, it is important to examine how impactful this method is from the perspective of students' learning experiences. Project-based learning involves many students in interactive activities that affect them both individually and in groups. This research is a quantitative study aimed at examining the role of socio-economic factors, entrepreneurship, and student learning motivation on the success of project-based learning in the International Business course, mediated by the variable of self-efficacy. The analysis technique used is Structural Equation Modelling (SEM). The population consists of Management students who are taking courses using project-based learning. Data was collected through questionnaires distributed to 270 student respondents. The tool used was SEM-PLS. The findings of this study reveal three interesting points. First, learning motivation has a positive effect on self-efficacy. Second, self-efficacy influences the success of project-based learning. Third, student learning motivation impacts the success of project-based learning through the mediation of self-efficacy. This means that the higher the learning motivation, the greater its effect on learning outcomes. It is important for lecturers to provide motivational support to students in order to achieve learning objectives.